1996
DOI: 10.1289/ehp.961041151
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of S-phenyl mercapturic acid and trans-trans-muconic acid as biomarkers for exposure to low concentrations of benzene.

Abstract: Phenol is not reliable as a biomarker for exposure to benzene at concentrations below 5 ppm (8-hr time-weighted average [TWA]). S-Phenylmercapturic acid (S-PMA) and trans-trans-muconic acid (tt-MA), two minor urinary metabolites of benzene, have been proposed as biomarkers for low-level exposures. The aim of this study was to compare their suitability as biomarkers. S-PMA and tt-MA were determined in 434 urine samples collected from 188 workers in various settings in the petrochemical industry and from 52 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 14 publications
4
59
0
2
Order By: Relevance
“…Nevertheless, the observation as a whole suggests that the effect should be small if present. Thus, the present survey not only supports the opinion that PMA is a good biomarker of benzene exposure 8,9,[15][16][17][18][19] , but has demonstrated that PMA is useful even under the condition of co-exposure to other aromatics and most probably to other solvents in general. The latter observation suggests that, as a benzene exposure marker, PMA is superior to mono-to tri-hydroxylated benzenes [phenol 27) , quinol 27) and catechol 27) , 1,2,4-benzenetriol 11) ] and t,t-muconic acid 13) , because the excretion of these urinary benzene metabolites other than PMA are all known to be suppressed by coexposure to other aromatics.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Nevertheless, the observation as a whole suggests that the effect should be small if present. Thus, the present survey not only supports the opinion that PMA is a good biomarker of benzene exposure 8,9,[15][16][17][18][19] , but has demonstrated that PMA is useful even under the condition of co-exposure to other aromatics and most probably to other solvents in general. The latter observation suggests that, as a benzene exposure marker, PMA is superior to mono-to tri-hydroxylated benzenes [phenol 27) , quinol 27) and catechol 27) , 1,2,4-benzenetriol 11) ] and t,t-muconic acid 13) , because the excretion of these urinary benzene metabolites other than PMA are all known to be suppressed by coexposure to other aromatics.…”
Section: Discussionsupporting
confidence: 83%
“…Major findings available in literature on quantitative relationship of PMA in end-of-shift urine with TWA benzene exposure 8,9,[15][16][17][18][19] are summarized in Table 4. The reported values for PMA corresponding to 1 ppm benzene cluster around 40 µg/g cr with two extremes of 12 and 58 µg/g cr.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of metabolite in urine prefer to analysis of benzene at blood because collection of urine is painless, easy to obtain, low in cost and easily performed even at subjects are far away from laboratory. An alternative approach involves measurement of the metabolites of benzene in urine including phenol, trans, trans-muconic acid (TTMA) and s-phenylmercapturic acid (SPMA) (ACGIH, 2005;Inoue et al 2000;Boogaard et al, 1996). TTMA and SPMA were proposed to replace phenol in biological monitoring of benzene (Boogaard et al, 1996;ACGIH, 2005) Benzene in the human system is subsequently oxidized to benzene oxide and in turn conjugated with glutathione to form SPMA that is excreted in the urine (15).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach involves measurement of the metabolites of benzene in urine including phenol, trans, trans-muconic acid (TTMA) and s-phenylmercapturic acid (SPMA) (ACGIH, 2005;Inoue et al 2000;Boogaard et al, 1996). TTMA and SPMA were proposed to replace phenol in biological monitoring of benzene (Boogaard et al, 1996;ACGIH, 2005) Benzene in the human system is subsequently oxidized to benzene oxide and in turn conjugated with glutathione to form SPMA that is excreted in the urine (15). SPMA derives solely from benzene metabolism and is a sensitive and specific biomarker of exposed benzene in low level (Van Sitter et al, 1993, Ghittori et al, 1996.…”
Section: Introductionmentioning
confidence: 99%